Testando a hipótese de passeio aleatório no mercado de ações brasileiro - Sales, Ludmilla Oliveira Ambrosi (2017)
This paper revisits the theory of market efficiency and analyzes the Brazilian capital market for a more recent period in order to verify if the improvement pointed out in the study by Bonomo (2002) persists, that is, if the reduction of inefficiency in the course of the Time is robust. The existence of autocorrelation may be an indication of abnormal returns if the strategies adopted exploit this correlation and generate an abnormal return. The autocorrelation tests adopted in the random walk literature, for the most part, do not take into account the Heteroscedasticity characteristic of financial assets and, therefore, this work seeks to apply Bartlett’s formula for non-linear processes in order to verify if existence Of autocorrelation between the Brazilian papers analyzed and if this is enough to generate an extraordinary return. Traditional statistical and correlation tests were applied together with random walk tests to verify if the Brazilian capital market is efficient in its weak form.